Proceedings of the IGSHPA Research Track 2022 2022
DOI: 10.22488/okstate.22.000038
|View full text |Cite
|
Sign up to set email alerts
|

Control strategy evaluation framework for ground source heat pumps using standing column wells

Abstract: Standing column wells (SCWs) are efficient ground heat exchangers (GHEs) that have a significant cost saving potential. Recent developments have shown that they can also adapt successfully to cold climates despite previous concerns about operating near the freezing point. Therefore, new research frontiers are now being explored as the integration of this type of GHE to a real case study building model has hardly been analyzed until now. An institutional building has been selected for a SCW demonstration projec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Along the same line, [22] found that the redesign of existing districts from a PED perspective should be directed towards the combination energy efficiency and energy flexibility strategies in order to obtain a positive balance even in the case of high population density, while [23,24] highlights the need for energy sharing and optimal control in energy communities.…”
Section: Positive Energy Districts and Energy Flexibilitymentioning
confidence: 99%
“…Along the same line, [22] found that the redesign of existing districts from a PED perspective should be directed towards the combination energy efficiency and energy flexibility strategies in order to obtain a positive balance even in the case of high population density, while [23,24] highlights the need for energy sharing and optimal control in energy communities.…”
Section: Positive Energy Districts and Energy Flexibilitymentioning
confidence: 99%